Hak Kepemilikan Komunal dalam Indikasi Geografis: Suatu Tinjauan Globalisasi Hukum - Taufitra, Ayang Ayu; Kurniawan, I Gede Agus (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
The urgency of this research is an effort to examine geographic indications (IG) in the perspective of legal globalization. This study aims to analyze the nature of communal ownership rights in GIs and the existence of GI communal ownership rights in the perspective of legal globalization. This research is a normative legal research with a concept and statutory approach. The results of the study show that the nature of communal ownership rights in GIs has its own characteristics that are different from other intellectual property rights. The nature of communal ownership rights in GI is a construction on the conception of ownership rights which are not only owned individually, but also include communal ownership. The essence of communal ownership rights in GIs has not actually received specific arrangements in various international rules and conventions. The existence of IG communal ownership rights in the perspective of legal globalization is actually still weak and needs to be strengthened. This strengthening is necessary to emphasize the style and characteristics of GI as intellectual property rights with special characteristics. This can be done by revising various international provisions governing GI as well as revising national rules that discuss GI where revisions are made to emphasize the characteristics of GI as separate intellectual property rights which are different from trademark rights and have special characteristics in the form of intellectual property rights. communal ownership. Keywords: Legal Globalization, Communal Property Rights, Geographical Indications.